Trio album, arrangements of favorite melodies for violin, violoncello, and piano - BIEDERMAN, Robert (G. Schirmer. Inc., 1937)
TreesnValsenBy the bend of the rivernRussian dancenSylvianThe Dresden ShepherdessnMah Lidy LounLondondery AirnJuramenElectric